PENERAPAN PENDEKATAN KETERAMPILAN PROSES DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SMP NEGERI 1 TUHEMBERUA TAHUN PELAJARAN 2010/2011 - Harefa, Amin Otoni (IKIP Gunungsitoli, 2010)
Abstract. Approach basic on skill process is knowledge guidance of intellectual skill development, physical and social that sourced from basic ability which is its principle of the skills had at studentsâ selfTarget of research (1). Depicting of is quality of study of mathematics through applying approach skill process, (2). Depicting result of learning student through approach skill process,(3). Proving by signifikan the quality of study of good mathematics by applying approach skill process, (4). Proving by signifikan mean result of learning good mathematics by applying approach skill process.Â Key Words:Â Approach on skill process,Â Learn result.